Transcriptional and Antagonistic Responses of Biocontrol Strain Lysobacter enzymogenes OH11 to the Plant Pathogenic Oomycete Pythium aphanidermatum - Zhao, Yangyang; Qian, Guoliang; Chen, Yuan; Du, Liangcheng; Liu, Fengquan (Frontiers in Microbiology, 2017)
Lysobacter enzymogenes is a ubiquitous, beneficial, plant-associated bacterium emerging as a novel biological control agent. It has the potential to become a new source of antimicrobial secondary metabolites such as the Heat-Stable Antifungal Factor (HSAF), which is a broad-spectrum antimycotic with a novel mode of action. However, very little information about how L. enzymogenes detects and responds to fungi or oomycetes has been reported. An in vitro confrontation bioassay between the pathogenic oomycete Pythium aphanidermatum and the biocontrol bacterial strain L. enzymogenes OH11 was used to analyze the transcriptional changes in the bacteria that were induced by the oomycetes. Analysis was performed at three time points of the interaction, starting before inhibition zone formation until inhibition zone formation. A L. enzymogenes OH11 DNA microarray was constructed for the analysis. Microarray analysis indicated that a wide range of genes belonging to 14 diverse functions in L. enzymogenes were affected by P. aphanidermatum as critical antagonistic effects occurred. L. enzymogenes detected and responded to the presence of P. aphanidermatum early, but alteration of gene expression typically occurred after inhibition zone formation. The presence of P. aphanidermatum increased the twitching motility and HSAF production in L. enzymogenes. We also performed a contact interaction between L. enzymogenes and P. aphanidermatum, and found that HSAF played a critical role in the interaction. Our experiments demonstrated that L. enzymogenes displayed transcriptional and antagonistic responses to P. aphanidermatum in order to gain advantages in the competition with this oomycete. This study revealed new insights into the interactions between bacteria and oomycete.